PELATIHAN MENULIS KARYA ILMIAH UNTUK MENINGKATKAN PRODUKTIVITAS PUBLIKASI MAHASISWA FKIP UNIVERSITAS ASAHAN - Wan Nurul Atikah Nasution; Eva Mizkat; Datulina Ginting; Rahma Yunita Ansi; Susi Masniari Nasution (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2026)
The ability to write scientific papers is one of the academic competencies that students must possess to support research activities, the preparation of final assignments, and scientific publications. However, many students still experience difficulties in writing scientific papers that meet academic standards and are worthy of publication. The lack of understanding of the structure of scientific articles, citation techniques, the use of reference management applications, and the journal publication process are factors that influence the low productivity of student publications. Therefore, this Community Service (PKM) activity was carried out in the form of Scientific Paper Writing Training to increase the publication productivity of students at the Faculty of Teacher Training and Education, Asahan University. The purpose of this activity is to improve students' knowledge, skills, and motivation in writing and publishing scientific papers in national and international journals. The methods used include lectures, discussions, demonstrations, workshops, scientific article writing practice, and mentoring in using the Mendeley application as a reference management tool. The activity was attended by FKIP students at Asahan University from various study programs. The training activity was held on December 8, 2025, in the FKIP classroom at Asahan University. This activity has proven effective in improving academic writing competency and student publication productivity.